IMPLIKASI KONFLIK HISTORIS ISLAM-KRISTEN BARAT TERHADAP MUNCULNYA STIGMATISASI PERMUSUHAN - Yusuf, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
The current conflict between Islam and Christian (west) originally rooted from the historical conflict which has happened for a long time ago. The conflict has been begun from the success of Islam expansion to western countries. The conflict has got worse when the west enables to move Islam domination in which it affected on the stigmatization on the followers. They discredited each other both in theology and other aspects. All conflicts, including Islam-Christian conflict is 'sunnatullah', something unavoidable, which bring both negative-destructive and positive-constructive effect. In fact,the conflict tends to be negative-destructive. Colonialism, which has been continually followed with missionarism and orientalism worsen the situation. This article discusses the implication of historical conflict on stigmatization done by the followers. Moreover, it tries to offer an alternative solution, that is, providing a dialogue as a bridge to resolve the conflict. It is expected to stifle the conflict and gradually to shift the conflict into a mutual understanding relationship.